Penanaman Nilai-Nilai Karakter Siswa Melalui Kacamata Pendidikan Agama Islam di Sekolah - Mhd. Fajar Siddik; Solihin Solihin; Muhammad Rifi Harahap; Hasrian Rudi Setiawan (SOKO GURU: Jurnal Ilmu Pendidikan, 2023)
The issue of the character of students or the character of this nation is the most important issue for the world of education in the country. The emergence of character education in Indonesia is marked by the decline in the morale of students, in this case the government must participate to improve character education in Indonesia.. Although in essence improving the character of the nation's children is the main task of education. The cultivation of character values is placed in as the core curriculum in the teaching and learning process in schools through Islamic subjects. This article aims to describe the cultivation of character values through Islamic religious education in schools. This study uses qualitative research with a literature study approach by collecting data from several books, journals, and websites. The results showed that character education must be carried out based on the values of religious teachings. Character education should not conflict with religion. This study uses qualitative research with a literature study approach by collecting data from several books, journals, and websites. The results showed that character education must be carried out based on the values of religious teachings. Character education should not conflict with religion.